Effects of poultry litter amended steer diets and subsequent manure collecting systems on nutrient recovery in composted manures - Lekasi, J.K.; Tanner, J.C.; Kimani, S.K.; Harris, P.J.C. (Informa UK Limited, 2006)
Concentrate feeds have become an important feature of dairy cattle diets on small-scale farms in the Central Kenya Highlands. Excreta derived from such diets can be of high quality if nutrient losses are minimized. Steers were fed a basal diet of Napier grass supplemented with either commercial dairy meal at 0.5% of liveweight (low concentrate - LC) or dairy meal (0.5% liveweight) plus poultry litter (0.5% liveweight) (high concentrate - HC). The amount of faeces and urine collected, and the dry matter, N and K contents of the resulting manure composted with wheat straw were significantly higher with the HC than with the LC diet, and this was the case also for P and Ca content when urine was added. Significant linear relationships were observed between the daily N intake and the daily N collected in faeces and urine. Dry matter, N, K and Ca were also higher when urine was added to the faeces and straw during accumulation than when urine was excluded, and this was the case also for P with high concentrate diets. Appropriate manure management could significantly improve nutrient conservation on smallholder farms in the Central Kenya Highlands and contribute to the sustainability of intensive cropping.